Strategi Partai Komunis Malaya Dalam Pergerakan Di Malaysia 1930-1968 - Samudra Eka Cipta; Wawan Darmawan (Prabayaksa: Journal of History Education, 2024)
The Communist Party of Malaya (PKM) employed a variety of strategies to disseminate its ideology among the general public. During the early 1920s, the communist movement utilized the "United Front" strategy, leveraging the Kuomintang party and Chinese schools as power bases, organizations, and publications to advance its influence. Following the establishment of the CCP in 1930, the communist strategy was to exploit prevailing conditions such as economic recession and the Sino-Japanese War to increase their influence among the people. During the Japanese occupation, the "United Front" strategy was again employed, this time the PKM formed an alliance with the British against the Japanese. The same strategy was employed in the post-war period by the PKM in their alliance with left-wing organizations against the returning British in Malaya, but ultimately proved unsuccessful. Concurrently, the PKM attempted to exert control over the Union workforce, but this was also unsuccessful. The setbacks faced by the PKM compelled it to adopt a more militant strategy through armed struggle. This article examines the various strategies employed by the PKM between 1930 and 1968 to expand their influence among the population.